The synergistic effect of microplastic and malathion exposure on fiddler crab Minuca ecuadoriensis microplastic bioaccumulation and survival - Cabrera, Marcela (2022)
We assessed the combined effects of polyethylene microplastic (MP) and malathion (MLT) on the survival of the fiddler crab Minuca ecuadoriensis, and MP tissue bioaccumulation in four treatments following 120 h exposure: T1) Control; T2) MLT 50 mg L− 1 ; T3) MP 200 mg L− 1 ; and T4) MLT (50 mg L− 1 ) + MP (200 mg L− 1 ). The highest mortality (80%) was in T4, followed by T2 (28%) and no mortality was in T3. Higher MP bioaccumulation was observed in T4 (572 items g tissue− 1 ) followed by T3 (70 items g tissue− 1 ). Our findings indicate that the synergistic effect of MLT and MP increased M. ecuadoriensis bioaccumulative capacity and decreases survival. Thus, as MP contamination in aquatic environments is ubiquitous, our study raises a warning on the synergistic effects of MP with other environmental contaminants and serves as a baseline for further studies.